تأثير المعالجة بثنائي الأمين (Putrescine) في نمو نباتات الفول, وتوزع محتواها من العناصر المعدنية في ظروف الملوحة (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
The interactive effect of NaCl salinity and putrescine on faba bean growth and ion (Na+, K+, and Cl-) distribution in roots and shoots was studied. Salinity decreased transpiration, shoot and root dry matter of faba bean plants. Putrescine application on the leaves or to the root medium, did not affect neither transpiration rate nor dry matter in the control or saline conditions. Ion distribution in roots and shoots was changed with putrescine treatment: Na+ and Cl- ion contents decreased in the shoots of salt stressed plants. K+ content increased in the roots and shoots of unstressed treated plants, but was not affected under saline conditions. The decrease of Na+ and Cl- contents in putrescine treatments under saline conditions and the increase of K+ content under control conditions did not improve plant growth, this suggests that Na+ and Cl- content in the salt stressed plants was not the limiting factor of growth and the same is true for  K+ contents in control plants.تمت دراسة التأثير المتبادل بين الملوحة ( 100 mM : NaCl ) والـ Putrescine في نمو نباتات الفول, وتوزع محتواها من( Na+, K+ والـ Cl- ) في كل من الجذور والفروع. خفضت الملوحة النتح والمادة الجافة في جذور نباتات الفول وفروعها, ولم يؤثر تطبيق الـ Putrescine, رشاً على الأوراق, أو مضافاً إلى وسط الجذور, في معدل النتح, أو في المادة الجافة عند النباتات المعالجة, أو غير المعالجة بالملوحة. أدت المعاملة بالـ Putrescine إلى تغيير توزع الأيونات في الجذور والفروع، فقد انخفض محتوى الفروع من الـ Na+ والـ Cl- في النباتات المجهدة ملحياً, وأدت هذه المعاملة إلى ازدياد محتوى الـ K+ في جذور النباتات غير المعاملة بالملوحة وفروعها, لكنه لم يتأثر في ظروف الملوحة. إن انخفاض محتوى الـ Na+ والـ Cl- , نتيجة المعالجة بالـ Putrescine, في ظروف الملوحة, وارتفاع محتوى الـ K+ في ظروف الشاهد, لم يحسن نمو النبات، وهذا يفترض أن محتوى الـ Na+ والـ Cl- في النباتات المجهدة ملحياً ليس هو العامل المحدد للنمو, وكذلك الأمر بالنسبة لمحتوى بالبوتاسيوم.